Combining of quantitative and qualitative analysis in risk management using Pareto distribution: A case study of an insurance company - Boudaoud, Khelid; Aicha, Khelid (International journal of economic perspectives, 2025)
The study aims to create a probability distribution that seeks to analyze and assess the main risks faced by the company. To this end, Pareto Distribution was used in risk management, which provides a useful analytical framework for many risks through its probabilistic distributions, ranking risks from the most impactful to the least impactful, achieving the principle of symmetry (80% of effects come from 20% of causes). This allows for the organization of risk mitigation measures at points of weakness. The results obtained through Pareto Distribution indicated that a small portion of the risks explain a large part of the potential losses for the company's portfolio in the future. Additionally, we found a relationship between the main risks and the strategic response adopted by the company, along with effect size from those risk-driving variables.